Pengaruh Kepemilikan Institusional, Profitabilitas, Kebijakan Hutang Dan Ukuran Perusahaan Terhadap Kebijakan Dividen (Studi Kasus Pada Perusahaan Food And Beverage Periode 2016-2018) - Indah Fatmawati; Rois Arifin; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis research was conducted at Food and Beverage companies listed on the Indonesia StockExchange. The purpose of this study is to determine and analyze the effect of InstitutionalOwnership, Profitability, Debt Policy and Company Size on Dividend Policy in Food andBeverage companies for the 2016-2018 period.The variables used are institutional ownership, profitability, debt policy and company size asthe independent variable, and dividend policy as the dependent variable. The data collectionmethod used is documentation. The data types in this study are secondary data. Theanalytical method used is multiple linear regression analysis, this study uses data fromcompanies listed on the Indonesia Stock Exchange in 2016-2018 and samples are taken usingpurposive sampling. The number of samples taken in this study were 10 companies.The results showed that institutional ownership and debt policy had no effect on dividendpolicy, profitability had a positive effect and company size had a negative effect on dividendpolicy.Keywords: Institutional Ownership, Profitability, Debt Policy, Firm Size, Dividend Policy.